HUBUNGAN KOMUNIKASI INTERNAL DENGAN MOTIVASI KERJA PEGAWAI (Studi di Puskesmas Brambang) - Elga Putra Windika; Hindyah Ike; Nurul Huda (Jurnal Keperawatan, 2014)
Communication employee at the health center are less effective Brambang result of less brave subordinatesin delivering opinions and suggestions to the boss so that the relationship with the head of the health centeremployees become less harmonious. The purpose of this study is to analyze the relationship between internalcommunication with employees on work motivationPuskesmas Brambang.The design of this study used a survey conducted in survey cross sectional. This study was conducted inPuskesmas Brambang Gudo Jombang, using the method of sampling the total number of samples 24employees. Data collection using questionnaires. Processing the data through the stages of Editing, Coding,Scoring, and Tabulating. Statistical tests using Spearmen Rank at the level of 5%.The results showed the price and the value of r at 0,500 probabillitas 0,013 < 0,05, then there is arelationship of internal communication with employees on work motivation Puskesmas Brambang. Relationsbetween the two variables is affected sex, age, length of service and education.Internal Communication employee at the health center are included in the category Brambang enough.Motivation of employees working at the health center are included in the category Brambang There wasrelationship and internal communication with employees on work motivation Puskesmas Brambang.Sugestion for management Puskesmas to increase employees on work motivation, for STIKES ICME giveninformation knowlege for reseacrh in the future.Keyword : Internal Communication, Work Motivation